Effect of Carbonization Step on Surface Character of Activated Carbon from Cassava Peels and Its Simple Application for BTEX Adsorption - Cucun Alep Riyanto; Alvama Pattiserlihun; Blessy Yemima Andiani; Ezra Kurniawan; Fahmi Puteri Perdani; Marcelino Kelpitna (Jurnal Kimia Sains dan Aplikasi, 2025)
Activated carbon is obtained from biomass waste because it is cheaper and renewable from an environmental perspective. In cassava peel biomass waste, it is necessary to study the effect of the carbonization stage on the surface character and pore distribution of the activated carbon obtained. In this research, the study of the impact of the carbonization stage is continued with the application of adsorption to volatile compounds, specifically benzene, toluene, ethylbenzene, and xylene (BTEX). This study conducted carbonization at 400°C (t: 60 minutes) followed by dual activation stages, namely chemical activation (carbon: H3PO4 30%, ratio 1:5, w/b) and physical activation (furnace, T: 600°C, t: 60 minutes). After that, the activated carbon from cassava peels (CPAC) was applied as an adsorbent for BTEX. The results showed that CPAC has an amorphous character with O-H, C-H, C≡C, C=C stretching, C-O, and C=N functional groups. The carbonization step changes pore properties. CPAC-202 (with carbonization) has a mesoporous character with a surface area up to 198.233 m2/g, with the surface dominated by C and O elements. The selectivity of BTEX gas adsorption is more significant for toluene using CPAC-202, with the best adsorption reaching 6.418 mg/L.